2018
DOI: 10.1111/1750-3841.14157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Canning and Freezing on the Nutritional Content of Apricots

Abstract: The apricot industry is limited by the short shelf life of the fruit and consumer belief that processed produce is not as nutritious as fresh. Assessing the nutritional content of canned and frozen apricots and determining that processed apricots can deliver nearly comparable nutrient levels to fresh apricots provides the evidence needed to dispel these misconceptions and potentially increase demand for processed apricots among consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…Lemmens et al (2011) found that beta-carotene bioaccessibility in carrots increased with increasing intensity of mechanical processing and increasing intensity of thermal processing [29]. Adkison et al (2018) reported that apricots exhibited large increases in beta-carotene after freezing (35%) [30]. Like our results, they reported a continued rise in beta-carotene (56%) after three months in frozen storage compared with fresh.…”
Section: Carotenoids (Lutein Lycopene Alpha-carotene Beta-carotene)supporting
confidence: 75%
“…Lemmens et al (2011) found that beta-carotene bioaccessibility in carrots increased with increasing intensity of mechanical processing and increasing intensity of thermal processing [29]. Adkison et al (2018) reported that apricots exhibited large increases in beta-carotene after freezing (35%) [30]. Like our results, they reported a continued rise in beta-carotene (56%) after three months in frozen storage compared with fresh.…”
Section: Carotenoids (Lutein Lycopene Alpha-carotene Beta-carotene)supporting
confidence: 75%
“…This can become an important factor for determining the bioavailability of nutraceutical factors from plants. Several researchers have reported an decrease in phytochemical content during processing (Aaby, Wrolstad, Ekeberg, & Skrede, 2007; Adkison, Biasi, Bikoba, Holstege, & Mitcham, 2018; Hoffmann‐Ribani, Huber, & Rodriguez‐Amaya, 2009; Igual, García‐Martínez, Camacho, & Martínez‐Navarrete, 2011; Rababah et al., 2010; Rawson et al., 2011) while others have reported an increase (Patras, Brunton, Butler, & Downey, 2009; Wani, Masoodi, Ahmad, & Mir, 2018; Zafrilla, Ferreres, & Tomás‐Barberán, 2001) or no change in phytochemicals (Jiratanan & Liu, 2004; Odriozola‐Serrano, Soliva‐Fortuny, & Martin‐Belloso, 2008). One of the important controllable factors for reducing the damage to phytochemicals in plant foods is the optimization of processing operations.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in AA with the intensity of thermal processing may be related to its thermal sensitivity, chemical degradation (oxidation of ascorbic acid to dehydroascorbic acid which leads to inactive products after hydrolysis and polymerisation), water solubility, and leaching (Dewanto et al ., 2002; Wang et al ., 2018). Similarly, the variation in both TFC and TPC among the treatments may be due to differences in the formation of non‐enzymatic browning products or release of bound phenolic compounds (by breaking the esterified and glycosylated bond) and deactivation of hydrolytic and oxidative enzymes which degrade phytonutrients (Patras et al ., 2009; Sharma et al ., 2015; Adkison et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%